The Quality of E-Government in Population Service in Bandung 2021 - Mulyadi, Annisa Meidina; Suwaryo, Utang; Sagita, Novie Indrawati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This study explains the quality of e-government in population service in Bandung City. E-Government is an activity or activity utilizing tools in the form of information technology in helping implement a government system so that it can run more efficiently. However, e-Government are still not running optimally. The theory used in this study is the e-Government Quality (e-GovQual). This study uses a qualitative descriptive research method. The data sources used are primary data and secondary data. As well as data collection techniques carried out by researchers, namely observation, in-depth interviews, and documentation. Based on the research that has been done, it is concluded that the quality of e-government at the Bandung City Population and Civil Registration Office is still not running optimally, indicated by data leaks and cybersecurity systems that are not yet qualified and services that can only be accessed via Android. Also, the features in the application cannot be used in real-time, but are opened only if there are human resource (HR) constraints in e-government management, which are also still very limited.